RESEARCH ON YOUNG LEARNERS: ADVANCING UNDERGRADUATE STUDENTS’ RESEARCH EXPERIENCE - Martin Kustati (Universitas Islam Negeri Imam Bonjol Padang, 2017)
Research for young learners has been receiving considerable attention from the respective worldeducation institutions due to its increasing importance for teaching demands. As a result, theresearch has taken enormous strides over the past few decades, which has had its significanceimplications for the teaching of young learners. This article thus far discusses the nature ofresearch in the area of young learners and then goes on to discuss its characterists, currenttrends, and process of research in the area of young learners. Next, it concludes with theresearch method that most commonly carried out by undergraduate students in their field ofstudy.